2015
DOI: 10.1021/acsnano.5b00716
|View full text |Cite
|
Sign up to set email alerts
|

Optics and Nonlinear Buckling Mechanics in Large-Area, Highly Stretchable Arrays of Plasmonic Nanostructures

Abstract: Large-scale, dense arrays of plasmonic nanodisks on low-modulus, high-elongation elastomeric substrates represent a class of tunable optical systems, with reversible ability to shift key optical resonances over a range of nearly 600 nm at near-infrared wavelengths. At the most extreme levels of mechanical deformation (strains >100%), nonlinear buckling processes transform initially planar arrays into three-dimensional configurations, in which the nanodisks rotate out of the plane to form linear arrays with "wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
92
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(98 citation statements)
references
References 14 publications
(19 reference statements)
6
92
0
Order By: Relevance
“…In these metasurfaces, each meta-atom is a high index nanopost acting as a short waveguide, which locally imposes a certain phase shift and polarization rotation. Several efforts have been made to transfer metasurfaces (mostly plasmonic ones) to flexible substrates with the aim of tuning their frequency response using substrate deformation [19][20][21][22][23][24][25]. Plasmonic metasurfaces, however, have low efficiencies especially in transmission mode, which in many situations make them impractical.Here, we introduce flexible metasurfaces based on a dielectric high contrast transmitarray platform that can be conformed to a non-planar arbitrarily shaped object to modify its optical properties at will.…”
mentioning
confidence: 99%
“…In these metasurfaces, each meta-atom is a high index nanopost acting as a short waveguide, which locally imposes a certain phase shift and polarization rotation. Several efforts have been made to transfer metasurfaces (mostly plasmonic ones) to flexible substrates with the aim of tuning their frequency response using substrate deformation [19][20][21][22][23][24][25]. Plasmonic metasurfaces, however, have low efficiencies especially in transmission mode, which in many situations make them impractical.Here, we introduce flexible metasurfaces based on a dielectric high contrast transmitarray platform that can be conformed to a non-planar arbitrarily shaped object to modify its optical properties at will.…”
mentioning
confidence: 99%
“…The integration of plasmonic nanoparticles on top of elastomeric substrates has enabled tuning of the plasmon modes (5)(6)(7)(8)(9)(10), but the resonances remain broad because of radiative damping. Although long-range coupling in periodic arrays can result in extremely narrow resonances (full width at half maximum (FWHM) linewidths <5 nm) (11)(12)(13), the design criteria for these lattice plasmon modes are stringent, and the quality of the arrays is fixed at the time of fabrication.…”
mentioning
confidence: 99%
“…EM metamaterials have potential for application in a wide variety of areas, in particular for sensing 10–15 . Inspired by the metamaterial approach, researchers have designed various sensors to diagnose strain or force telemetrically 2–4, 16–19 . Previously reported strain- or force-measurement devices typically comprise metallic resonators, such as split-ring resonators (SRRs) 2–4 , or complex metallic nanostructures 18–22 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the sensors usually need to be adhered to the surface of the tested materials, which can cause measurement errors and lead to difficulties in measuring objects with complicated structures. Recent studies have shown that either linear or nonlinear performance can be achieved by introducing elastomer materials such as polydimethylsiloxane into metal nanoparticle structures 19, 23–26 , which has enabled the development of flexible EM devices that can be mechanically tuned with large strain deformation and have broad applications in biomedical engineering. These nanostructures usually require complex fabrication processes and operate in high-frequency ranges, such as near-infrared wavelengths 19 or in the visible region 21, 22 .…”
Section: Introductionmentioning
confidence: 99%